2021
DOI: 10.1002/jmrs.555
|View full text |Cite
|
Sign up to set email alerts
|

Immersive virtual reality simulated learning environment versus role‐play for empathic clinical communication training

Abstract: Introduction The use of immersive virtual reality simulated learning environments (VR SLEs) for improving clinical communication can offer desirable qualities including repetition and determinism in a safe environment. The aim of this study was to establish whether the mode of delivery, VR SLE versus clinical role‐play, could have a measurable effect on clinical empathic communication skills for MRI scenarios. Methods A split‐cohort study was performed with trainee practitioners (n = 70) and qualified practiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“… 17 , 18 A final 4 of 22 articles focused on measuring empathy response after VR/AR intervention and were grouped in a separate category. 22 , 23 , 25 , 35 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 , 18 A final 4 of 22 articles focused on measuring empathy response after VR/AR intervention and were grouped in a separate category. 22 , 23 , 25 , 35 …”
Section: Resultsmentioning
confidence: 99%
“…VR-based studies contained a large variety of interventions—all with the aim of improving medical communication. Different intervention types included: 4 of 17 studies using VR to simulate a patient encounter, 15 , 31 , 33 , 36 4 of 17 implementing a VR teaching curriculum, 16 , 23 , 33 , 35 2 of 17 providing a VR video game experience, 18 , 22 4 of 17 using VR to educate patients, 20 , 29 , 30 , 34 2 of 17 using the headsets to view video recordings, 17 , 25 and 3 of 17 using headsets to view 3D models. Interventions involving 3D model viewing were mostly associated with patient education, 28 - 30 or facilitation of faster and easier preoperative planning.…”
Section: Resultsmentioning
confidence: 99%
“…Hypothesis 1a : A previous study showed that VR in a simulated learning environment can improve empathic clinical communication score by 0.3-1.15 points with a standard deviation (σ) of 0.3-1.1 [ 26 ]. To detect a statistically significant change in our study, a sample size of 68 participants is needed to obtain a medium-to-large effect size ( d =0.5-0.8) with a power level of .80 and an alpha of .05 [ 26 , 27 ]. We will compare the number of identified contributing factors (after reading the event vs after VR training) by using a within-subject 2-tailed, 2-sample t test with the significance level set to .05.…”
Section: Methodsmentioning
confidence: 99%
“…Each conversation is automatically mapped against pre-determined template responses and a transcript can be reviewed at the end of the consultation alongside expert feedback on the student’s chosen response. Preliminary data from these modules suggests VR-based training was effective in eliciting empathic communication skills - possibly even more so than those trained in real-life role play practice [39] . These benefits likely derive from VRs ability to provide unlimited practice with minimal pressure, both of which can be limiting factors in conventionally interview training with simulated patients.…”
Section: Choosing the Right Learning Tool For The Right Purposementioning
confidence: 99%
“…
Fig. 7 Effective Digital Delivery Methods and the Domains of Learning [13] , [19] , [38] , [39] , [40] , [41] , [42] .
…”
Section: Choosing the Right Learning Tool For The Right Purposementioning
confidence: 99%